A Study on Economic Analysis of Financial Conditions of Indian Government Banks: Examining the Impact of Government Control on Indian Banks (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Measured by share of deposits, 83 percent of the banking business in India is in the hands of state or nationalized banks, which are banks that are owned by the government, in some, increasingly less clear-cut way. Moreover, even the non-nationalized banks are subject to extensive regulations on who they can lend to, in addition to the more standard prudential regulations. Government control over banks has always had its fans, ranging from Lenin to Gerschenkron. While there are those who have emphasized the political importance of public control over banking, most arguments for nationalizing banks are based on the premise that profit maximizing lenders do not necessarily deliver credit where the social returns are the highest. The Indian government, when nationalizing all the larger Indian banks in 1969, argued that banking was “inspired by a larger social purpose” and must “subserve national priorities and objectives such as rapid growth in agriculture, small industry and exports. The current paper highlights the various aspect of banking reform in India.